Prescription errors and pharmacist intervention at outpatient pharmacy of Chitwan Medical College - Poudel, R S; Piryani, R M; Shrestha, S; Prajapati, A; Adhikari, B (Journal of Chitwan Medical College, 2015)
Prescribing errors are harmful to the patients. The role of pharmacist in reducing potential harm from prescription errors have been highlighted by several studies. This study aimed to evaluate the drug related prescription error and pharmacist intervention at outpatient pharmacy of Chitwan Medical College Teaching Hospital. A cross-sectional study was conducted in the outpatient Pharmacy of Chitwan Medical College Teaching Hospital from November 2014 to December 2014. The outpatient pharmacist randomly selected 5000 prescription and checked for drug related prescription error using prescription error checklist. The pharmacist discussed the prescription errors with the prescriber. The prescriptions that were corrected by the prescribers were considered as pharmacist intervened prescriptions (pharmacist intervention). Descriptive statistics including Chi-square test were done for statistical analysis using IBM-SPSS version 20. Out of 5000 prescriptions 176 drug related prescription error was found. The commonest error was dose and dosing frequency error (39.2%), duplication (33.5%) and dosage form related error (19.3%). Most of the prescription errors were noted while prescribing antimicrobial drugs (27.8%), proton pump inhibitors (15.9%) and NSAIDs (12.5%). The pharmacist’s recommendation was accepted by prescriber in 90.3% of prescription . Chi-square test showed significant association (p=0.019) between prescription errors and pharmacist intervention. Pharmacist intervention can reduce the drug related prescription error, so the pharmacist and clinician need to strongly work together for reducing overall prescriptions error.